2021
DOI: 10.4269/ajtmh.20-1156
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Development of Miliary Pulmonary Tuberculosis in a Patient with Peritoneal Tuberculosis after COVID-19 Upper Respiratory Tract Infection

Abstract: We report a 29-year-old patient who presented with coronavirus disease 2019 (COVID-19) upper respiratory tract infection in addition to clinical, laboratory, and radiological findings highly suggestive of peritoneal tuberculosis (TB) without pulmonary involvement. Two weeks after the resolution of COVID-19 infection, he presented with shortness of breath and oxygen desaturation requiring intubation and admission to the intensive care unit. The workup confirmed miliary pulmonary TB. The patient subsequently imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Most researchers regard pulmonary tuberculosis as a risk factor for the severe course of a new coronavirus infection ( Chen et al, 2020 ; Gupta et al, 2020 ; Khayat et al, 2021 ). The reverse negative interaction of these diseases has also been described – for example, an increased risk of a latent infection turning into an active form of tuberculosis against the background of COVID-19, due to the depletion of CD4 + T cells ( Elziny et al, 2021 ; Starshinova et al, 2021; Visca et al, 2021 ). Several studies have noted an aggravation of the course of both diseases in their mutual existence due to common social, epidemiological, and clinical determinants ( Mousquer et al, 2021 ; Ritacco and Kantor, 2020 ; Yang and Lu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers regard pulmonary tuberculosis as a risk factor for the severe course of a new coronavirus infection ( Chen et al, 2020 ; Gupta et al, 2020 ; Khayat et al, 2021 ). The reverse negative interaction of these diseases has also been described – for example, an increased risk of a latent infection turning into an active form of tuberculosis against the background of COVID-19, due to the depletion of CD4 + T cells ( Elziny et al, 2021 ; Starshinova et al, 2021; Visca et al, 2021 ). Several studies have noted an aggravation of the course of both diseases in their mutual existence due to common social, epidemiological, and clinical determinants ( Mousquer et al, 2021 ; Ritacco and Kantor, 2020 ; Yang and Lu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[14] Stochino et al reported 20 patients with TB and COVID-19 coinfection, of which 3 patients were diagnosed with extrapulmonary TB. [15] Mustafa et al identified the development of miliary TB in a patient with peritoneal TB after COVID-19 infection, [16] and Yao et al described 2 cases of active pulmonary TB infection from latent pulmonary TB infection. [17] However, to the best of our knowledge, all cases reported have been adults, and reports describing a flare-up of TB infection following COVID-19 exposure, in the paediatric age group, have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Outro fator determinante à evolução do quadro descrito pode ser atribuído à infecção prévia de CO-VID-19 nos três meses que antecederam sua internação hospitalar pela tuberculose miliar. Estudos recentes observaram que a infecção pelo vírus SARS-CoV-2 pode levar à uma disfunção imunológica, através da depleção de células T e diminuição na sua funcionalidade, facilitando um estado de imunossupressão e servindo, também, como uma ferramenta facilitadora à reativação de tuberculose (18) .…”
Section: Discussionunclassified